A blast from the past: Civilians immediate psychological reactions and associative memory of prior events following exploding bus in Israel. (30th December 2016) - Ben-Ezra, Menachem; Pitcho-Prelorentzos, Shani; Mahat-Shamir, Michal
Abstract: This study examined the association between self-report associative memories of prior traumatic events and psychological distress up to 48 h after a terror attack. To date, the number of studies that examined this association is very small and most were conducted weeks or even months post event. For this purpose, we examined the association between self-report associative memories of prior traumatic events beyond factors such as previous exposure to trauma, political shift and sense of safety. The results showed that self-report associative memories of prior traumatic events were significantly associated with psychological distress. These results could be explained by the similarity and recency effects. Highlights: Little is known about the releationship between associative memories of prior events and psychological distress immediately (up to 48 h) after a terror attack. We examined the correlations between self-report associative memories of prior events and psychological trauma beyond key factors such as previous exposure to trauma, political shift and sense of safety. Positive correlation was found between associative memories of prior events that were either recent of similar to the terror attack and psychological distress. The results could be explained by the similarity and recency effects.